The Approach of Al-Zarkashi to The Roles of Mutlaq and Muqayyad in Understanding the Divine Revelation - Yusuf Olawale Owa-Onire Uthman (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
This study intends to focus on reviewing some previously recorded materials to discuss the approach of az-Zarkashi (d. 794/1392, see page 3 footnote for his short history) to the roles of an absolute word (mutlaq) and delimited word (muqayyad) in understanding the divine revelations. The method of az-Zarkashi is been chosen for thğis research due to his huge influence in the fields of principles jurisprudence (Usul al-fıqh), Quranic science, and its exegesis. The efforts employed by az-Zarkashi in the book named Bahru’l-Muhit fi Usul al-Fiqh on the topic of this paper which is mutlaq and muqayyad in the section of Usul al-fiqh, and his work on Quranic sciences (see also page 3) increases the interest in studying the research topic of our current paper. Without a doubt, many of the ambiguities about the Quranic exegesis and Hadith and the likes will be in the clarified stage by applying the available theory in the az-Zarkashi's work regarding the terms mutlaq and muqayyad. However, this study aims to shed more light on the way of deriving the proper understanding and better interpretative method to the two Islamic devıne revelations; which are basically known as the Qur'an and the prophetic tradition (Hadith).